2017
DOI: 10.4236/pp.2017.811026
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility of Paracetamol with Pediatric Suspensions Containing Amoxicillin, Azithromycin and Cefuroxime Axetil

Abstract: The main objective of this work was to use the Differential Scanning Calorimetry (DSC) and FTIR spectroscopy to study the possible drug-drug or drug-excipient (s) interaction in case of concomitant oral administration of paracetamol with the most common used antibiotics for children. Amoxicillin, azithromycin, cefuroxime axetil and their commercially available suspensions, Amoxil ® , Azithromax ® and Zinnat ® were used. DSC curves for paracetamol, pure antibiotics, commercially available antibiotics and all bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Meanwhile, the endothermic peak at 143.27 °C along with shoulder peak provide enough insight regarding the formation of cocrystal [ 60 ]. Moreover, the shifting of endothermic peaks of AZT-PCM physical mixture (1:1, w / w ) to lower temperature previously reported, which indicating strong interactions between APIs [ 61 ]. The survey of 50 samples was evaluated, the results showed 51% cocrystals melting point in between those of respective APIs and their coformer, while 39% were lower than both of the components, only for 4% the value was similar to either the API or conformer, and 6% had higher melting than the parent material.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Meanwhile, the endothermic peak at 143.27 °C along with shoulder peak provide enough insight regarding the formation of cocrystal [ 60 ]. Moreover, the shifting of endothermic peaks of AZT-PCM physical mixture (1:1, w / w ) to lower temperature previously reported, which indicating strong interactions between APIs [ 61 ]. The survey of 50 samples was evaluated, the results showed 51% cocrystals melting point in between those of respective APIs and their coformer, while 39% were lower than both of the components, only for 4% the value was similar to either the API or conformer, and 6% had higher melting than the parent material.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, DSC analysis reveals the formation of new cocrystal material [ 63 , 64 ]. Furthermore, a different position of the melting peak also suggested physical interactions developed between both the APIs in their resulted cocrystal [ 61 ]. The binary phase diagram is also given in Figure S1 shows the physical interaction between corresponding constituents.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC curves of BFO (loaded with amoxicillin) and the 3D-printed scaffolds are presented in Figure 3. It was observed that a minor endothermic peak as a result of dehydration of AMX occurs at ~ 100 o C. A minor broad endothermic peak, due to AMX fusion degradation at 190-~222.3˚C was also observed [18]. Figure 3 shows that a steep exothermal peak occurs at ~230 o C, which is attributed to a mass loss of the BFO due to its decomposition to Fe(OH)3 and Bi(OH)3 metastable states [12].…”
Section: Resultsmentioning
confidence: 92%
“…The presence of amoxicillin leads to the merging of the peak associated with water loss with the peak of thermal transition in amoxicillin, potentially connected to its phase changes, as observed in the thermogram of Fig. 4a (Maswadeh, 2017). This occurs due to amoxicillin's strong a nity for water (Narkar et al 2010).…”
Section: Characterization Of the Microparticlesmentioning
confidence: 90%